Penerapan Asas Keadilan Pada Transaksi Penyimpanan Dana Nasabah Di Bank Syariah Berdasarkan Akad Mudharabah - Siti Nur Shoimah; Dyah Ochtorina Susanti (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2020)
This research is motivated by the fact that it does not include clauses related to the risk of the Bank or the Customer in the mudharabah agreements in the customer deposit funds in Islamic Banking (Sharia Banking), if at any time the business of managing a Islamic Bank fund suffers, even though there are also Customer funds in the business, and it’s not balanced, because maybe only one party, the Customer or the Bank, bears the risk of loss. This imbalance then causes injustice, even though justice is a shariah requirement in the distribution of results from a business activity. Research that uses the normative legal research with the statute approach, and conceptual approach, results in the finding that the principle of justice in customer deposit funds in Islamic Banking based on mudharabah agreements is realized in the form of profit sharing system in the form of proportional and balanced benefits and risks.